Correlation studies in avocado (Persea americana ) accessions for morphological and biochemical characters (Current Horticulture, 2024)
In present study, correlation coefficients were estimated for different morphological and biochemical traits in 83 avocado (Persea  americana Mill.) accessions of South India. The fruit weight, fruit length, fruit width, pulp weight and seed weight showed highly  significant positive correlations with fruit yield, while peel per cent showed negative correlation with fruit yield. These traits can  be utilized for selection of high-yielding genotypes. The total phenols content has positive correlation with DPPH antioxidant  activity. The dry-matter content of pulp showed highly significant positive correlation with oil content of fresh and dry pulp,  while moisture content in pulp showed negative correlation with oil content of fresh pulp. The dry-matter content and moisture  content of pulp can be utilized for selection of high oil-yielding accessions.
Keywords: Oil content; Selection; Correlation; Dry-matter; FRAP